The Methodological and Didactic Aspects of Comprehensive Greening of Educational Process Towards Sustainable University - Yuriy Tunytsya; Ihor Soloviy; Vasyl Lavnyy (Journal of Sustainability Perspectives, 2021)
The process of greening education is aimed to educate new generation with the holistic vision of the real world challenges, attitudes of responsibility and active social behavior as an agent of sustainability transformations. The methodological and didactic aspects of comprehensive greening of educational process discussed. It’s based on integration the competence and the whole school approaches, sustainable life style and green campus practices into sustainable university model. The preconditions for systemic and holistic integration of the sustainability principles into all fields of the university life are identified. Especial attention is paid to the recent experiences of the Ukrainian National Forestry University as the leading university in Ukraine in implementing the concept of greening higher education in Ukraine and member of new networking project “V4 Green Universities” supported by the Visegrad Fund.